Possible association between metabolic dysfunction-associated steatotic liver disease predictors and hand grip strength - Suyeon Lee; Jong-Koo Kim; Taesic Lee (Scientific Reports)
Abstract Both Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) and sarcopenia are associated with numerous chronic diseases, and the link between the two broad-spectrum phenotypes has been extensively researched. We focused on the relationship between the hepatic steatosis index (HSI) and hand grip strength (HGS). The Korean National Health and Nutrition Examination Surveys (2014–2019) were utilized to identify the association between estimated MASLD (eMASLD) and muscle strength. HSI determined eMASLD status, and HGS evaluated muscle strength. The HSI demonstrated a positive correlation with HGS. The alanine transaminase (ALT)/aspartate aminotransferase (AST) ratio and diabetes among the five components of HSI exhibited significant relationships with HGS in men and women. The robust linearity between HSI and HGS was observed in multivariate models and stratified analyses, particularly in older non-diabetic men with a higher body mass index (BMI) and young women without diabetes. However, younger men and older women exhibited nonlinear associations influenced by the ALT/AST ratio, BMI, and diabetes. After adjusting HGS with BMI, a significant negative association between HSI and muscle strength was observed, particularly in women. The disruption in linearity was influenced by the ALT/AST ratio, particularly in men with diabetes. Our findings highlight the complex interplay between HSI and HGS. The relationship between the two broad-range phenotypes was observed, and liver profiles influenced the linearity.